Semi-Automatic Child Rescuing BOT in Deep Borewell - Nithyaprakash R.; Shankar S.; Naveen Kumar R.; Praveen Kumar S.; Seenivasa R.; Naveen Prasath S. (E3S Web of Conferences, 2023)
Rescue operations for people trapped in deep borewells provide a serious problem needing both advanced robotic technology and human expertise. This abstract focuses on the creation of a revolutionary machine-human rescuing robot that is specifically designed to respond to emergencies in deep borewells. the complicated nature of deep borewell rescues, which includes technical challenges, time-sensitive situations, and the requirement for swift and accurate action. It draws attention to the drawbacks of conventional rescue techniques and promotes the creation of a flexible robotic system that can work in tandem with human rescuers. The suggested robot is built as a hybrid system that combines human control with autonomous functionality. To deliver real-time data and visual feedback from the borewell inside, it integrates specialized sensors, cameras, and communication tools. The borewell rescue robot’s, structural frame work consists of two cylindrical pipes fastened vertically with the help of T shaped square rod, these cylindrical pipes acts as a holding platform for children hands. Lower end of the pipes are provided with mechanical straps which in turn are actuated by BLCD motors with human rescuers is a crucial component of its functionality. Skilled operators can control the robot’s movements in real time thanks to remote operating interfaces and haptic feedback systems. The significance of the robot-human rescue team in deep borewell crises is emphasized in the abstract.